Thermal and Gas Adsorption Properties of Tröger's Base/Diaza‐cyclooctane Hybrid Ladder Polymers. Issue 7 (7th May 2021) - Inoue, Keiki; Selyanchyn, Roman; Fujikawa, Shigenori; Ishiwari, Fumitaka; Fukushima, Takanori
Abstract: A polymer of intrinsic microporosity (PIM) consisting of Tröger's base (TB) undergoes ring opening of the bicyclic amine upon N ‐methylation followed by alkaline hydrolysis, resulting in a hybrid ladder polymer that contains diazacyclooctane (DACO) units with tert ‐ and sec ‐amino groups. The hybrid ladder polymers with various TB/DACO ratios can be prepared depending on the reaction conditions. Here we report a systematic study on the effect of DACO content on the thermal and gas adsorption properties of the hybrid ladder polymer. Using a PIM derived from 2, 5‐diamino‐ p ‐xylene, we prepared hybrid ladder polymers with a DACO content ranging from 19% to 55% while having a similar molecular weight. The thermal stability of the hybrid ladder polymers, evaluated by thermogravimetric analysis, is decreased with the increase in DACO content. Based on gas adsorption measurements, the increase in DACO content results in the decrease in the BET surface area but improves the gas adsorption selectivity for CO2 against N2, likely due to high basicity of the sec ‐amino group of DACO unit. This result demonstrates that the partial TB‐to‐DACO conversion of the TB‐based PIM may provide a simple but useful strategy to design polymer materials that enable selective CO2 capture and/or separation. Abstract : Hybrid ladder polymers containing Tröger's base (TB) and diazacyclooctane (DACO) units in the main chain were systematically synthesized with various contents of DACO unit, which endows the polymers with modified basicity and conformational flexibility. Notably, the presence of DACO unit improves the adsorption selectivity of CO2 against N2 compared with an original TB‐based polymer, while partly maintaining its intrinsic microporosity.